2011
DOI: 10.1371/journal.pone.0022159
|View full text |Cite
|
Sign up to set email alerts
|

Timing Actions to Avoid Refractoriness: A Simple Solution for Streaming Sensory Signals

Abstract: Segmenting self- from allo-generated signals is crucial for active sensory processing. We report a dynamic filter used by South American pulse electric fish to distinguish active electro-sensory signals carried by their own electric discharges from other concomitant electrical stimuli (i.e. communication signals). The filter has a sensory component, consisting of an onset type central electro-sensory neuron, and a motor component, consisting of a change in the fish's discharge rate when allo-generated electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Spherical neurons show a one-spike phenotype (Soares et al, 2002), as shown by whole-cell patch recordings in brain slices of the electrosensory lobe (Nogueria et al, 2006;Nogueira and Caputi, 2011) (Fig.1). This suggests the presence of a low-threshold, noninactivating K + conductance and a hyperpolarization-activated I h .…”
Section: The Phenotype: the One-spike-onset Neuronsmentioning
confidence: 81%
See 4 more Smart Citations
“…Spherical neurons show a one-spike phenotype (Soares et al, 2002), as shown by whole-cell patch recordings in brain slices of the electrosensory lobe (Nogueria et al, 2006;Nogueira and Caputi, 2011) (Fig.1). This suggests the presence of a low-threshold, noninactivating K + conductance and a hyperpolarization-activated I h .…”
Section: The Phenotype: the One-spike-onset Neuronsmentioning
confidence: 81%
“…Four lines of argument support this affirmation (Nogueira et al, 2006;Nogueira and Caputi, 2011): (1) subthreshold pulses of increasing intensities are followed by a reduction of the depolarization caused by a second pulse (Fig.3A); (2) action potentials are followed by an increase in cell membrane conductance (Fig.3B) and an increase of spike threshold (Fig.3C) and (3) a long refractory period of similar time course (Fig.3D); and (4) this long refractory period is reduced under the treatment with low doses of the K + channel blocker 4AP (compare Fig.3D and 3E). …”
Section: The Phenotype: the One-spike-onset Neuronsmentioning
confidence: 91%
See 3 more Smart Citations